Production Forecasting Analysis of CV. Peduli Pangan Indonesia - Fikri Akmal Zain; Wiwik Handayani (International Forum of Researchers and Lecturers, 2025)
With the rising demand in the food sector, particularly for ready-made spices, CV. Peduli Pangan, which focuses on producing sachets of pepper, has a notable chance for expansion. To address this demand, accurate forecasting of production is essential for guiding choices related to production planning. Forecasting is an important tool for decision-making that underpins various manufacturing and service sectors.This research aims to estimate the ideal production quantity of pepper sachets over the next 12 periods. Regression analysis is utilized to identify the best-fitting model based on the gathered data, facilitating an exploration of how important factors affect production. The resulting regression formula shows that the production levels are impacted by the cost of raw materials (HBB), product defects (PG), and workforce (TK). The constant figure of 11,109.687 signifies the fundamental production level when these factors are not considered. If all other factors are ignored, a decrease in production volume occurs when the raw material price (X1_HBB) is -0.15 and the defect rate (X2_PG) is -0.617. On the other hand, production volume rises if the labor factor (X3_TK) is valued positively at 37.317. This forecasting model is designed to aid CV. Peduli Pangan in making informed and precise production choices.